PERBEDAAN NYERI PUNGGUNG SEBELUM DENGAN SESUDAH PEMBERIAN KOMPRES HANGAT PADA IBU HAMIL TRIMESTER III - Santhi, Putu Kartik (Fakultas Ilmu Kesehatan, 2025)
Back pain is a common complaint among third-trimester pregnant women due to physiological, hormonal, and postural changes. This study aims to determine the difference in back pain intensity before and after warm compress therapy among third-trimester pregnant women at Puskesmas Sawan II. The research used a pre-experimental one-group pretest-posttest design with the NRS pain scale as an instrument. A total of 30 participants were selected using purposive sampling. Warm compresses at 40°C were applied twice daily for three days. The median pain score before the intervention was 4.00 and decreased to 1.00 after. The Wilcoxon test showed a significant difference with p = 0.000 (p < 0.05). These results indicate that warm compresses are effective in reducing back pain intensity. Future studies are recommended to include direct supervision during the intervention.